الحرمان العاطفي وعلاقته الادمان على مواقع التواصل الاجتماعي لدى تلاميذ سنة أولى ثانوي - نسرين بوردحة; كريمة عبادو (جامعة الوادي - University of Eloued, 2025)
"هدفت الدراسة الحالية الى التعرف على العلاقة بين الحرمان العاطفي والادمان على مواقع التواصل الاجتماعي لدى عينة من تلاميذ السنة اولى ثانوي بلدية قمار ولاية الوادي، وقد تكونت عينة الدراسة من (150) تلميذا وتلميذة من تلاميذ اولى ثانوي للشعب (علوم تجريبية / آداب وفلسفة ) بثانوية تم اختيارهم بطريقة عشوائية . وقد تم استخدام المنهج الوصفي الارتباطي وذلك لمناسبته أهداف الدراسة ، كما تم تطبيق مقياس الحرمان العاطفي والادمان على مواقع التواصل الاجتماعي تبنينا مقياس ل ""المنيزل ""(2016) . وتوصلت الدراسة الى وجود علاقة ارتباطية موجبة عند مستوى الدلالة (0,01) بين الحرمان العاطفي والادمان على مواقع التواصل الاجتماعي وكما أظهرت ايضا ان مستوى الحرمان العاطفي لدى تلاميذ سنة اولى ثانوي جاء بمستوى متوسط بالإضافة الى مستوى الادمان على مواقع التواصل الاجتماعي ايضا جاء متوسط كما توصلت الى عدم وجود فروق ذات دلالة احصائية عند مستوى الدلالة (0.05) بين متوسطات الحرمان العاطفي تبعا لمتغير التخصص الدراسي ، وكذلك عدم وجود فروق ذات دلالة احصائية عند مستوى الدلالة (0.05) بين متوسطات الادمان على مواقع التواصل الاجتماعي تبعا لمتغير التخصص الدراسي." The current study aimed to identify the relationship between emotional deprivation and addiction to social networking sites among a sample of first-year secondary school students in the city of El Oued, municipality of Ghommar, and to study the differences between them in deprivation and addiction to social networking sites in light of some variables. The study sample consisted of (150) male and female students from the first year of secondary school in the (Experimental Sciences / Arts and Philosophy) sections in a secondary school who were randomly selected. The descriptive correlational approach was used due to its suitability for the study objectives. The emotional deprivation and addiction to social networking sites scale "Al-Munizeel" (2016) was also used. The study found that there is a positive correlation at the significance level (0.01) between emotional deprivation and addiction to social networking sites. It also showed that the level of emotional deprivation among first-year secondary school students was at an average level, in addition to the level of addiction to social networking sites also being average. It also found that there were no statistically significant differences at the significance level (0.05) Between the averages of emotional deprivation according to the variable (Academic specialization) There were also no statistically significant differences at the significance level (0.05) between the averages of social media addiction according to the variable (Academic specialization (.
مذكرة ماستر قسم علم النفس وعلوم التربية تخصص إرشاد وتوجيه
Keywords: الحرمان العاطفي; الادمان على مواقع التواصل الاجتماعي; تلاميذ سنة أولى ثانوي; Emotional deprivation; Social media addiction; First-year high school students